Accounting Practices in Determining the Cost of the Metatah Ceremony in the Adult Initiation Rite in Hindu Tradition - Komang Yudha Manggala Putra; M. Ali Fikri (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to explore accounting practices in determining the costs of the Metatah ceremony, a rite of passage into adulthood in the Hindu tradition. Using an ethnographic approach, the research involves informants consisting of students, families, and relatives who have previously performed the Metatah ceremony in the city of Mataram. The results show that the cost determination practices in the Metatah ceremony reflect the complexity between the community's spiritual and economic aspects. The cost components analyzed include offerings (banten), fees for the pedanda (ceremonial leader), ceremonial decorations, traditional clothing, music and traditional dance performances, guest banquets, and documentation expenses. Each cost component shows significant variation, reflecting differences in families’ economic capabilities as well as diverse interpretations in carrying out the ceremony. Interestingly, despite the variations in costs, the study shows that the Hindu community has developed various adaptive strategies to ensure the ceremony is carried out in accordance with their economic capabilities without diminishing its spiritual value.